The tenacity of trust in petrochemical communities: Reckoning with risk on the Fawley Waterside (1997–2019). (September 2022) - Brown, David; Mah, Alice; Walker, Gordon
Around the world, people living close to polluting industries have different perceptions of the risks of toxic exposure, ranging from anger to acceptance to denial. We draw attention to a case with relatively high levels of social trust, but also relatively high levels of risk perception: the communities living adjacent to the Fawley (UK) oil refinery and petrochemical complex, a site that has been operated by Esso since the early 1950s. Our findings are based on a novel comparative analysis of two qualitative studies of local risk perceptions in Fawley conducted more than two decades apart in 1997 and 2019, incorporating focus group and individual interviews with residents, alongside documentary analysis and stakeholder interviews. Perceptions of risk and trust in the local polluting industry have fluctuated over the years, with unease never far from the surface as industrial employment has slowly contracted. Yet overall, the picture in 2019 was not too dissimilar from that in 1997: while community–industry relations were strained amidst periodic risk incidents and a sense of decline, a cautious sense of trust in the polluting enterprise had endured, based on a delicate balance of heritage, risk, and recognition. We draw attention to the residents' careful reckoning with risks over time and the tenacity of social trust as an act of negotiation that took risk into account but also included other important factors such as recognition and reciprocity. Local risk perceptions in Fawley are closely bound up with the residents' shared industrial heritage and enduring perceptions of Esso as a 'good neighbour'. Our longitudinal analysis allowed us to reflect on changes over time in Fawley, providing greater temporal depth to the risk perception literature.